Knowledge on Ice - Kullerud, Lars (Arctic Portal, 2011)
Mr. Lars Kullerud, University of the Arctic president, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.